(untitled) (International Journal of Engineering and Computer Science, 2015)
Static Synchronous Compensator (STATCOM) regulates the voltage and corrects the power factor at the point of common coupling (PCC) by injecting reactive power. Also, this device plays a vital role as a stability aid for small and large transient disturbances in an interconnected power system. This paper deals only with power-factor correction mode and show the Total Harmonic Distortion (THD) in source current is drastically reduced fuzzy controller is included in the STATCOM control circuit..The use of STATCOM a FACTS device is increasing in the power system for enhancing power transfer capability and dynamic reactive power support in power system. In this paper a Fuzzy logic new control method for STATCOM is proposed and applied for damping oscillations. Simulations using MATLAB / SIMULINK are carried out to verify the performance of the proposed controller. Significant improvement of damping oscillations has been achieved with the proposed fuzzy logic supplementary controller. The results of these studies show that the designed controller has an excellent capability in damping power system oscillations.